2006
DOI: 10.1016/j.bbrc.2006.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Herc5-mediated ISGylation of novel target proteins

Abstract: ISG15, a protein containing two ubiquitin-like domains, is an interferon-stimulated gene product that functions in antiviral response and is conjugated to various cellular proteins (ISGylation) upon interferon stimulation. ISGylation occurs via a pathway similar to the pathway for ubiquitination that requires the sequential action of E1/E2/E3: The E1 (UBE1L), E2 (UbcH8), and E3 (Efp/Herc5) enzymes for ISGylation have been hitherto identified. In this study, we identified six novel candidate target proteins for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 20 publications
(24 reference statements)
1
62
0
Order By: Relevance
“…However, EFP has little effect on the total ISGylation when co-transfected with ISG15, UBE1L, and UbcH8 into 293T cells [11]. The direct comparison between EFP and Herc5 are reported by a recent paper [19]. Among the tested four targets, EFP can increase the ISGylation of tubulin as well as Herc5 and weakly increase the conjugation of two other targets.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, EFP has little effect on the total ISGylation when co-transfected with ISG15, UBE1L, and UbcH8 into 293T cells [11]. The direct comparison between EFP and Herc5 are reported by a recent paper [19]. Among the tested four targets, EFP can increase the ISGylation of tubulin as well as Herc5 and weakly increase the conjugation of two other targets.…”
Section: Discussionmentioning
confidence: 95%
“…Among the tested four targets, EFP can increase the ISGylation of tubulin as well as Herc5 and weakly increase the conjugation of two other targets. However, Herc5 can increase the ISGylation of all four targets [19]. We also tested the effect of Herc5 on the ISGylation of 14-3-3σ.…”
Section: Discussionmentioning
confidence: 98%
“…We therefore investigated whether PKR is modified by ISG15. UBE1L, mUbcH8, His 6 -tagged ISG15, and HA-tagged PKR were expressed in HEK293T cells together with the nonspecific ISG15 ligase Herc5 to improve ISGylation (11)(12)(13). ISGylated proteins were purified by Ni-NTA-agarose chromatography and subjected to Western blotting against an anti-HA antibody to detect the ISGylation of HA-PKR (Fig.…”
Section: Isg15mentioning
confidence: 99%
“…The ubiquitin E2 enzymes UbcH6 and UbcH8 also function as ISG15-conjugating enzymes (6 -8). In contrast to ubiquitin ligases, only a few ISG15 ligases have been identified, including EFP (9), HHARI (10), Herc5 (11)(12)(13), and Herc6 (14,15). USP18 (UBP43) is an isopeptidase that removes ISG15 from its substrates (16).…”
mentioning
confidence: 99%
“…Unlike ubiquitination, ISGylation typically does not promote degradation of the target proteins. A couple of proteomics studies have identified .100 cellular proteins as potential targets of ISGylation (32)(33)(34)(35). These proteins cover a wide spectrum of biological processes, including transcriptional regulation, signal transduction, inflammation, and control of cell growth.…”
mentioning
confidence: 99%